Etika zastiranja in podrejenosti žensk v islamu - Pešić, Daša (Analiza: časopis za kritično misel, 2025)
The Ethics of Veiling and Submission of Women in IslamThe article focuses on Islamic ethics, the veiling of women in Islam, and the Western criticism of this phenomenon. It describes how Islamic ethics affect interpersonal relationships, whereby religious commandments and principles contribute to establishing orderly coexistence between people. Particular emphasis is placed on the veiling of women in the Islamic religion, where different interpretations and practices are manifested because of a complex cultural and religious framework. It analyses how the veiling of women stems from religious beliefs but, at the same time, faces diverse interpretations and understandings in different societies. The article deals with the free choice of female veiling and how it is defined and conditioned in different societies. The whole discussion raises questions about diversity, culture, gender equality, and freedom of religious choice, which are embedded in the complexity of the relationship between Islam, Western culture, and the veiling of women.
Keywords: Islam; Koran; woman; veiling; Western culture; subjugation